Integrated Coastal Zone Management for Sustainable Ecotourism in Kalangan Hamlet, Pulau Pahawang Village, Lampung: A Case Study - Reza, Muhammad; Julian, David; Putra, Muhamad Gilang Arindra; Azkia, Lana Izzul (Jurnal Biologi Tropis, 2024)
Kalangan Hamlet is one of the coastal communities in Pahawang Island Village, Lampung. It has abundant natural resources and offers prospects as a tourist destination. It is located away from Pahawang Island, so the area is considerably behind in terms of tourism management. The aim of the research was to develop effective strategies for managing the coastal areas of Kalangan Hamlet. The strategies had been suggested to contribute to Kalangan Hamlet's potential for coastal tourism growth. Data was collected using survey and observation methods, with respondents chosen through the snowball sampling technique. The collected data was analyzed using Strengths, Weakness, Opportunities, and Thread (SWOT) analysis and Analytic Hierarchy Process (AHP). The primary strategy for managing the coastal areas of Kalangan Hamlet involves enhancing infrastructure to support tourism, while simultaneously prioritizing the preservation of the natural ecosystem and ensuring the well-being of the local population. This approach balances economic development with environmental sustainability and social equity, thereby fostering a holistic and sustainable tourism model.